Is it safe to remove an infected cardiac implantable electronic device at the time of heart transplantation? Report of two cases. Issue 1 (14th October 2019) - Donato‐Santana, Christian; Loebe, Matthias; Brozzi, Nicolas; Chaparro, Sandra; Bauerlein, Eugene J; Badiye, Amit; Ghodsizad, Ali; Simkins, Jacques
Abstract: Cardiac implantable electronic device (CIED) infections are treated with antibiotics and device explantation. Lack of CIED removal is associated with infection recurrence. However, CIED removal can be associated with major complications including death. We reported two patients with advanced heart disease who developed CIED infection due Staphylococcus epidermidis while awaiting for orthotopic heart transplantation (OHT). Both patients were managed with a different approach. They were treated with antibiotic therapy and had their CIED removal postponed until OHT. Both patients were kept on suppressive antibiotic treatment until undergoing simultaneous OHT and removal of infected CIED. None of the patients had infection recurrence. Large studies are needed to assess whether the approach of delaying CIED removal until OHT is safe among carefully selected patients with CIED infection.